2016
DOI: 10.2196/mhealth.5120
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Experiences Using a Commercially Available Monitor to Self-Track Their Physical Activity

Abstract: BackgroundPhysical activity contributes to older adults’ autonomy, mobility, and quality of life as they age, yet fewer than 1 in 5 engage in activities as recommended. Many older adults track their exercise using pencil and paper, or their memory. Commercially available physical activity monitors (PAM) have the potential to facilitate these tracking practices and, in turn, physical activity. An assessment of older adults’ long-term experiences with PAM is needed to understand this potential.ObjectiveTo assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 22 publications
7
108
4
Order By: Relevance
“…2) that sync with smartphones were perceived as useful and acceptable in a small sample of 32 adults over age 50 [47]. Another study by McMahon and colleagues evaluated the short-and long-term experiences of adults >70 years old with the Fitbit One activity tracker and found that it was easy to use, useful, and acceptable at 10 weeks and 8 months [48], though there were lower survey ratings by participants >80 years old.…”
Section: Potential Applications Of Gerontechnologies For Older Adultsmentioning
confidence: 99%
“…2) that sync with smartphones were perceived as useful and acceptable in a small sample of 32 adults over age 50 [47]. Another study by McMahon and colleagues evaluated the short-and long-term experiences of adults >70 years old with the Fitbit One activity tracker and found that it was easy to use, useful, and acceptable at 10 weeks and 8 months [48], though there were lower survey ratings by participants >80 years old.…”
Section: Potential Applications Of Gerontechnologies For Older Adultsmentioning
confidence: 99%
“…This study raised the question of how to motivate individuals to achieve further gains after initial success. Finally, another study suggested that new tracker designs and features may be needed for increasing physical activity in people 70 years of age and older [22]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have explored activity tracker use mostly at the initial stages of use [3,7,[36][37] and have not systematically evaluated the spectrum of features used, liked, and wanted by adults aged 65 and older.…”
Section: Comparison With Prior Workmentioning
confidence: 99%